A Practical Algorithm for the Management of Superficial Folliculitis of the Scalp: 10 Years of Clinical and Dermoscopy Experience - Starace, Michela; Yamagata, João Paulo; Cortez de Almeida, Rita Fernanda; Frattini, Simone; Bruni, Francesca; Alessandrini, Aurora; Iorizzo, Matilde; Fernandes Melo, Daniel; Neri, Iria; Piraccini, Bianca Maria (Dermatology Practical & Conceptual, 2023)
Introduction: Superficial folliculitis of the scalp (SFS) is a common complaint in clinical practice, and initial presentation may be difficult to differentiate as they may appear very similar to each other.Objectives: The aim of this thesis is to describe the pathologies that occur clinically as folliculitis of the scalp, identify their causes and characteristics and create a standardized classification.Methods: This is a retrospective clinical, dermoscopic and histopathological study over 10 years of dermatologic consultations. Only individuals with a confirmed diagnosis of SFS (updated diagnostic criteria or biopsy) were included.Results: In this review, we describe the various clinical features of different causes of SFS in ninety-nine cases and divided into infectious due to fungus, bacteria, or virus and inflammatory conditions such as rosacea, acneiform eruption and Ofuji syndrome.Conclusions: The clinician must differentiate SFS from other underlying scarring disorders to prevent poorer outcomes. We created an algorithm to help the clinician reach a proper diagnosis.